﻿Antitumor activity of the novel pyridine derivative - Ekaterina V. Blinova; Anna V. Epishkina; Oksana M. Tumutolova; Olga N. Deryabina; Sofia Ya. Skachilova; Mihail Yu. Kudriavtsev; Evgenia V. Shikh; Olga S. Vavilova; Yulia S. Gilevskaya; Gordey V. Brykin; Anna A. Makhrova; Dmitry S. Blinov (Belgorod National Research University, 2022)
Introduction: The study aim was to explore a toxicological property and antitumor action of the novel pyridine derivative LHT-17-19 in cell culture and on experimental models of lung cancer in mice. Materials and methods: The study was performed on male and female ICR(CD-1), male BALB/c, male BALB/c nu/nu mice. Pyridine derivative (LHT-17-19) was studied as water-soluble pharmaceutical substance. Acute toxicity was evaluated in groups of 5 animals, and the results were analyzed by Finney. Antitumor and antimetastatic activity was studied in syngeneic and xenograft models of lung cancer in mice. Results and discussion: LHT-17-19 belongs to class 3 of the toxicity classification of chemicals in accordance with GOST 12.1.007-76. The substance demonstrated an antitumor and antimetastatic property in mice with syngeneic tumor Lewis lung carcinoma as well as on the heterotopic tumor model of non-small cell lung cancer in humanized animals. Conclusion: LHT-17-19 belongs to class 3 of the toxicity classification of chemicals in accordance with WHO recommendation. LHT-17-19 exerts antitumor and antimetastatic property on both syngeneic and patient-derived lung cancer xenograft murine models. Graphical abstract